Patella Eversion in Knee Arthroplasty: Does it lead to an adverse outcome?. Issue 5 (31st May 2017) - Reid, Michael; Booth, Grant; Khan, Riaz JK; Janes, Greg
Objectives: Proponents of minimally invasive knee replacements argue that retracting rather than everting the patella results in quicker postoperative recovery and improved function compared to the standard approach. We aimed to investigate this in a group of patients undergoing knee arthroplasty using a standard medial parapatellar approach. Methods: In a prospective randomized double-blinded study sixty-eight patients undergoing total knee arthroplasty through a standard medial parapatellar approach were assigned to either retraction or eversion of the patella. An independent observer assessed the flexion and secondary outcome measures of Oxford knee score, the SF12 score, visual analog pain scores, range of motion data and radiographs preoperatively, at three months and at one-year post surgery. Results: Early (3 month) follow-up showed no significant difference between eversion and subluxation in flexion (mean and 95%CI, 101°± 5.37 vs 102°±4.14) Oxford knee scores (25±3 vs 27±2.69), SF12 or visual analog pain scores (1.9±0.54 vs 1.1±0.44). A statistically significant improvement in extension was found (-3.9°±1.12 vs 2.0°±0.91 (p=0.034)) but this was not thought to be clinically significant. There was no difference in any outcomes at one year. There was a significant difference in implant malpositioning in the subluxation group with increased percentage lateral tibial overhang (0.45±0.39 vs 1.84±0.82 (p=0.005)) but this did not correlate with functional outcome. There was no statistical difference in alignment between the two groups (178.29°±0.84 vs 178.18°±0.78). There was no difference between the two groups in Insall-Salvati Ratio (1.15±0.06 vs 1.12±0.06) although there was a correlation to a reduction in the ratio and functional outcome. There were two partial divisions of the patella tendon in the retraction group, but no patella related complications in the eversion group. Conclusion: Retracting rather than everting the patella during total knee arthroplasty results in no significant clinical benefit in the early to medium term. There is no increase in patella tendon shortening as a result of eversion rather than subluxation.